2019
DOI: 10.1177/0306624x19849562
|View full text |Cite
|
Sign up to set email alerts
|

Theta/SMR Neurofeedback Training Works Well for Some Forensic Psychiatric Patients, But Not for Others: A Sham-Controlled Clinical Case Series

Abstract: Electroencephalographic (EEG) neurofeedback could be a promising treatment for forensic psychiatric patients. Increasing evidence shows some patients are unable to regulate cortical activity. Before neurofeedback can be applied successfully, research is needed to investigate the interpersonal mechanisms responsible for patients’ ability to respond to neurofeedback. A single-case experimental design allows for close monitoring of individual patients, providing valuable information about patients’ response to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
2
2
0
Order By: Relevance
“…All the inmates in the NFB group got benefit from the treatment according to the improvement of their clinical symptoms, and this benefit was higher than in the control group. The current results are equivalent to those reported by a recent study reporting an improvement in behavior and impulsivity in a small group of forensic psychiatric individuals (Fielenbach et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…All the inmates in the NFB group got benefit from the treatment according to the improvement of their clinical symptoms, and this benefit was higher than in the control group. The current results are equivalent to those reported by a recent study reporting an improvement in behavior and impulsivity in a small group of forensic psychiatric individuals (Fielenbach et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…All the inmates in the NFB group got benefit from the treatment according to the improvement of their clinical symptoms, and this benefit was higher than in the control group. The current results are equivalent to those reported by a recent study reporting an improvement in behavior and impulsivity in a small group of forensic psychiatric individuals (Fielenbach et al, 2019). When analyzing the evolution of the clinical symptoms from the temporal perspective along the period of treatment, there were two clearly differentiated periods: first one, from the beginning Mcs1) to Session 16 (Mcs4, with significant between-group differences in the "mean clinical state."…”
Section: Discussionsupporting
confidence: 86%
“…2019 ), while some other studies could not attribute the findings of decreased impulsivity and craving directly to the SMR NF ( Fielenbach et al. 2018 , 2019 ). Based on several clinical findings of comorbid ADHD in patients with substance use disorder, the Peniston Protocol was further modified by Scott–Kaiser, who combined the EEG beta band and the SMR with the established AT training ( Scott and Kaiser 1998 ; Scott et al.…”
Section: Introductionmentioning
confidence: 94%
“…Besides the RCT design, four patients were additionally examined in an N-of-1 study design [10]. Results of the N-of-1 study showed that three patients completed all study phases, none of the patients followed the training like planned and the behavioral measures varied between the patients [23].…”
Section: Possibilities and Limitations Of N-of-1 Studiesmentioning
confidence: 99%